Identification of the Intracellular Gate for a Member of the Equilibrative Nucleoside Transporter (ENT) Family - Valdés, Raquel (American Society for Biochemistry and Molecular Biology, 2014)
Equilibrative nucleoside transporters of the SLC29 family play important roles in many physiological and pharmacological processes, including import of drugs for treatment of cancer, AIDS, cardiovascular, and parasitic diseases. However, no crystal structure is available for any member of this family. In previous studies we generated a computational model of the Leishmania donovani nucleoside transporter 1.1 (LdNT1.1) that captured this permease in the outward-closed conformation, and we identified the extracellular gate. In the present study we have modeled the inward-closed conformation of LdNT1.1 using the crystal structure of the Escherichia coli fucose transporter FucP and have identified four transmembrane helices whose ends close to form a predicted intracellular gate. We have tested this prediction by site-directed mutagenesis of relevant helix residues and by cross-linking of introduced cysteine pairs. The results are consistent with the predictions of the computational model and suggest that a similarly constituted gate operates in other members of the equilibrative nucleoside transporter family.